A conformação dos caminhos do Estado de São Paulo: breves correlações com seu desenvolvimento urbano e econômico - Taís Schiavon (Confins)
To understand the changes occurred in the current scenario of the São Paulo city leads to the study of its composition and regional articulation. Founded in 1554, the village of Piratininga has its historical development marked by inexpressiveness in its economic and territorial conformation. With the process of articulation of its primary roads, we can note the diversification of the local and regional services, process that culminates with the consolidation of the principal axes of articulation of the city, that being reaffirmed with the establishment of railroads, further boosting local growth and regional articulation. This article seeks to show how this conformation was articulated, from the understanding of the articulation of its primary roads, railways and highways, and, the resulting urban conformation.